2‑(Pyridin-2-yl)isopropyl (PIP) Amine: An Enabling Directing Group for Divergent and Asymmetric Functionalization of Unactivated Methylene C(sp3)–H Bonds - Zhang, Qi; Shi, Bing-Feng (Accounts of chemical research, 2021)
Conspectus Directing group (DG) assistance provides a good solution to the problems of reactivity and selectivity, two of the fundamental challenges in C(sp3)–H activation. However, the activation of unbiased methylene C(sp3)–H bonds remains challenging due to the high heterolytic bond dissociation energy and substantial steric hindrance. Two main strategies have been developed thus far, that is, use of a strongly coordinating bidentate DG pioneered by Daugulis and use of a weakly coordinating monodentate DG accelerated by pyridine-type ligands, as disclosed by Yu. The seminal work by Daugulis sparked significant interest in the application of the monoanionic bidentate auxiliary in aliphatic C–H activation reactions. Our research has focused on enabling the divergent functionalization and enantiotopic differentiation of unactivated methylene C–H bonds. Inspired by the structure of bidentate 8-aminoquinoline and the accelerating effect of the gem-dimethyl moiety in cyclometalations, we developed a strongly coordinating bidentate 2-(pyridine-yl)isopropyl (PIP) amine DG consisting of a pyridyl group, a gem-dimethyl moiety, and an amino group, which enabled the divergent functionalization of unactivated β-methylene C(sp3)–H bonds to forge C–O, C–N, C–C, and C–F bonds with palladium catalysts. The exclusive β-selectivity was ascribed to the preferential formation of kinetically favored [5,5]-bicyclic palladacycle intermediates. DFT calculations revealed that the well-designed gem-dimethyl group was responsible for the lowered energy and compressed bite angle of the key transition state related to C–H cleavage. More recently, the combination of PIP amine with axially chiral ligands was found to promote asymmetric functionalization of unbiased methylene C(sp3)–H bonds, a challenging research topic in the area of C–H activation that remains to be addressed. Two different types of axially chiral ligands, namely, non-C 2-symmetric chiral phosphoric acids (CPAs) and 3,3′-disubstituted BINOLs, have been developed. The former enabled Pd(II)-catalyzed inter- and intramolecular arylation of unbiased methylene C(sp3)–H bonds with high enantioselectivity, whereas the latter promoted a series of asymmetric functionalization reactions, such as alkynylation, arylation, alkenylation/aza-Wacker cyclization, and intramolecular amidation. The unexpectedly high stereocontrol compared with other bidentate DGs might be attributable to steric communication between the ligand and gem-dimethyl moiety of PIP amine. Thus far, the combination of PIP amine DG with 3,3′-disubstituted BINOL ligands is arguably the most general strategy for asymmetric functionalization of unbiased methylene C(sp3)–H bonds. Finally, the ease of installation and removal of PIP under mild conditions and synthetic applications are described.